2020
DOI: 10.1177/0886260519900299
|View full text |Cite
|
Sign up to set email alerts
|

Examining Spatial Variability in the Association Between Male Partner Alcohol Misuse and Intimate Partner Violence Against Women in Ghana: A GWR Analysis

Abstract: Globally, it is estimated that about 30% of ever-partnered women have experienced some form of intimate partner violence (IPV)—physical assault, sexual assault, or emotional abuse. The prevalence of IPV in sub-Saharan Africa is considerably higher than the global estimate. In Ghana, it is estimated that 24% of women have experienced physical and/or sexual IPV in their lifetime. Studies point to the association between alcohol misuse by intimate male partners and violence against women. However, there has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…This finding showed that there is spatial variation in the distribution of IPV within South Africa. This is in line with existing evidence from Ghana [18], Uganda [19] and Ethiopia [5]. A plausible justification in support of our findings could be the pervasiveness of misconceptions about IPV and prevailing cultural beliefs that reinforce acts that fall under the category of IPV [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding showed that there is spatial variation in the distribution of IPV within South Africa. This is in line with existing evidence from Ghana [18], Uganda [19] and Ethiopia [5]. A plausible justification in support of our findings could be the pervasiveness of misconceptions about IPV and prevailing cultural beliefs that reinforce acts that fall under the category of IPV [33].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies conducted in South Africa indicate that IPV is associated with several factors such as age [13], multiple sexual partnerships [14], childhood experience of abuse [15], as well as engagement in transactional sex and health inequalities [14,16]. Beyond these associated factors, evidence from recent studies conducted in Ethiopia [5,17], Ghana [18], Uganda [19], Nigeria [6] and Afghanistan [8] suggest that there are spatial variations in the distribution of IPV across the respective countries that have been minimally explored in extant literature.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a substantial body of research is acknowledging the importance of contextual factors underlying IPV (Gracia et al, 2021, 2018, 2015). This realization is motivating researchers to explore the spatial dimensions of the phenomenon (Amegbor et al, 2021; Amegbor & Rosenberg, 2019; Angaw et al, 2021; Gracia et al, 2015; Fontes et al, 2018; Oliveira et al, 2019; Montoriol et al, 2018; Seid et al, 2021; Tusa et al, 2022). Regional patterns in IPV have been examined using choropleth maps (Fontes et al, 2018; Montoriol et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…It indicates the need to go beyond individual and household level variables (Gracia et al, 2015), and study community-level determinants of IPV (Seid et al, 2021). Spatial analytic methods provide an important method to study spatial variations in IPV, the influence of community characteristics, and the interaction between neighboring areas on IPV (Amegbor et al, 2021; Amegbor & Rosenberg, 2019; Angaw et al, 2021; Fontes et al, 2018; Gracia et al, 2021, 2018, 2015, 2014; Montoriol et al, 2018; Oliveira et al, 2019; Seid et al, 2021; Tusa et al, 2022). However, it is an emerging area of research, and evidence linking IPV to neighborhood features is still weak (Beyer et al, 2015; Pinchevsky & Wright, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is literature about the perpetration of IPV in Sub-Saharan Africa and Ghana (Addo-Lartey et al, 2019;Adomako & Darkwa Baffour, 2019;Amegbor, Yankey, Rosenberg, & Sabel, 2020;Apatinga & Tenkorang, 2020;Baffoe-Whyte & Sossou, 2019;Cofie, 2018;Dako-Gyeke et al, 2019;Dery, 2019;Dickson et al, 2020;Doat, Negarandeh, & Hasanpour, 2019;Issahaku, 2015;Owusu-Addo et al, 2018;E. Y. Tenkorang, 2019), no single study has been done with the factors that led to male partners' perpetration of violence against their female HIV positive partners.…”
Section: The Theoretical Basis Of Intimate Partner Violence Perpetrationmentioning
confidence: 99%